Analysis of Flexural Strength Test Results of Coconut Fiber and Corn Husk Composite for Hanging Rack - Hadi, Syamsul; Sudrajat, Bangkit Agung (Politeknik Negeri Ujung Pandang, 2020)
The wood demand for construction, buildings and furniture is always increasing, while the availability of wood continues to decline with the growth of the wood industry. The purpose of this study was to determine the best flexural strength of the variation of composite board resin material with filler fibers of Coconut Fiber and Corn Husk (CFCH) with comparative specimens of particle boards and Sengon wood. Preparation of composite specimens from Yucalac 157 BQTN-EX polyester resin type added by CFCH fillers with different weight fractions, composite specimens were made accordance with ASTM-D 7264 standard size. Analysis of test data using One-wayAnovaÂ approach. The best percentage results on the composition of the weight of the hanging rackcomposite with the ratio of filler CFCH was 4.5%: 4.5% (1: 1) with 91% hardener resin, and the weight fractions of CFCH was affected to the flexural strengthcomposite, because Fcalculated> Ftable (15.05 > 5.14).